SISTEM SAPAAN DALAM WAYANG KULIT - Nurhayati, Endang (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2008)
This article is about a research study conducted to describe the system,type, and function of form of address in wayang kulit, the Javanese leather-puppetshadow play. The subject under study was a recording of such a play titled KarnaTandhing performed by Timbul Hadiprayitna as the puppet master. The researchmethod applied was descriptive in nature. The research data were obtained bymeans of a listen-and-write technique and analyzed by means of contextualinterpretation.The research results are as follows. 1. The system of form of address inwayang kulit consists of aspects of (1) relation between the addresser andaddressee, (2) sex/gender, (3) setting (place, time, and atmosphere), (4) purpose,(5) honoring, (6) doer, vocation, or profession, (7) marriage and love, (8) mentionof dwelling place, (9) religion and belief, (10) use of pronoun, (11) zero, and (12)mention of specific identity. In type, the form of address can be, among others, (1)a pronoun, (2) a proper name: a pre-adult name, an alternative name, or dasanama,(3) a title attributed due to position of authority, (4) a name others use to call one,(5) a hereditary form of address, (6) paraban